(untitled) (Bangladesh Journal of Agriculture, 2023)
A study was carried out with tomato at the research field of Regional Agricultural Research Station of BARI, Cumilla during two consecutive years 2019-20 and 2020-21. The objective was to evaluate the yield response and nitrogen use efficiency (NUE) of tomato (variety BARI Tomato-15) and to suggest the source and the rate of N fertilizer recommendation for tomato. The experiment was laid out in a RCBD design with three N sources (PU, NCU and DAP) and two N rates (100% and 125% of recommendation as per FRG-2018) replicated three times. In the first year, prilled urea (PU), neem coated urea (NCU) and DAP were used but in the second year DAP was replaced by urea super granule (USG). The recommended dose of N for tomato was 120 kg ha-1. Results revealed that between two rates of N application the yield was the maximum (77.4 t ha-1 and 60.3 t ha-1 in two years, respectively with 125% of RD. The highest agronomic use efficiency of nitrogen (NAUE) was obtained from 100% RD of N as DAP (150.0 kg kg-1) and 125% RD of N as NCU (133.3 kg kg-1). The lowest N use efficiency was observed in 100% PU (84.2 kg kg-1) and 100% NCU (40.8 kg kg-1) treated plots. Due to optimal plant growth, the neem-coated urea treatment yielded little higher than PU treatment. Bangladesh J. Agri. 2023, 48(1): 92-100